No Relationships Between the Within-Subjects’ Variability of Pain Intensity Reports and Variability of Other Bodily Sensations Reports - Agostinho, Mariana; Canaipa, Rita; Honigman, Liat; Treister, Roi (Frontiers in Neuroscience, 2019)
Purpose The subjective nature of pain assessment and its large variance negatively affect patient–health care provider communication and reduce the assay sensitivity of pain clinical trials. Given the lack of an objective gold standard measure, identifying the source (true or error) of the within-subject variability of pain reports is a challenge. By assessing the within-subjects variability of pain and taste reports, alongside with interoceptive measures, the current study is aimed to investigate if the ability to reliably report bodily sensations is a cross-modal characteristic. Patients and Methods This prospective study enrolled healthy volunteers from local universities. After consenting, subjects underwent the Focus Analgesia Selection Task (FAST), to assess within-subjects variability of pain reports in response to experimental noxious stimuli; a taste task, which similarly assesses within-subjects variability of tastes (salty and sweet) intensity reports; and the heartbeat perception task, an interoceptive task aimed to assess how accurate subjects are in monitoring and reporting their own heartbeat. In addition, all subjects completed the Multidimensional Assessment of Interoceptive Awareness (MAIA), the Perceived Stress Scale (PSS), and Hospital Anxiety and Depression Scale (HADS). Spearman’s correlations were used to assess relations between all measures. Results Sixty healthy volunteers were recruited. Variability of intensity reports of different modalities were independent of each other (P > 0.05 for all correlations). The only correlation found was within modality, between variability of intensity reports of salt and sweet tastes (Spearman’s r = 0.477, P < 0.001). No correlations were found between any of the task results and questionnaire results. Conclusion Within-subjects variability of pain reports do not relate to variability of reports of other modalities or to interoceptive awareness. Further research is ongoing to investigate the clinical relevance of within-subjects’ variability of pain reports.